Machine learning for identifying risk of death in patients with severe fever with thrombocytopenia syndrome - He, Qionghan; You, Zihao; Dong, Qiuping; Guo, Jiale; Zhang, Zhaoru (Frontiers in Microbiology, 2024)
Background: Severe fever with thrombocytopenia syndrome (SFTS) has attracted attention due to the rising incidence and high severity and mortality rates. This study aims to construct a machine learning (ML) model to identify SFTS patients at high risk of death early in hospital admission, and to provide early intensive intervention with a view to reducing the risk of death.Methods: Data of patients hospitalized for SFTS in two hospitals were collected as training and validation sets, respectively, and six ML methods were used to construct the models using the screened variables as features. The performance of the models was comprehensively evaluated and the best model was selected for interpretation and development of an online web calculator for application.Results: A total of 483 participants were enrolled in the study and 96 (19.88%) patients died due to SFTS.After a comprehensive evaluation, the XGBoost-based model performs best: the AUC scores for the training and validation sets are 0.962 and 0.997.Using ML can be a good way to identify high risk individuals in SFTS patients. We can use this model to identify patients at high risk of death early in their admission and manage them intensively at an early stage.